Ghosts of White Nights: A Freemason in the Net of Afterlife, The Maiden Drowned in May and the King Solomon’s Spirit - Nikolai N. Podosokorsky (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
In 1846-1848 three mystic texts of young F.M. Dostoevsky (not to mention his other works) were published in A.A. Kraevsky’s journal Otechestvennye Zapiski (Notes of the Fatherland), namely: The Double, The Landlady and White Nights. All of them are permeated with Gnostic and occult motifs. The novel White Nights, according to our hypothesis, tells about the postmortem pains of Petersburg ghosts that are doomed to roam the city, suffer from loneliness and dream of their past incarnation because they have “so little of the real life” but “their own life” where they anyway have “no one whom… you can say a word to”. There are a lot of hints in the text that the protagonist – the Dreamer – was a freemason before and possibly killed in a fire, and Nasten’ka whom he meets is a ghost of a suicide drown girl forced to wander between her past dwelling and the place where she died. The article analyzes the Masonic subtext of the novel dedicated to Dostoevsky’s friend of youth, the poet A.N. Pleshcheev who wrote several Masonic hymns. White Nights characters think the ideal to be in the mutual “fraternity” and actualize a number of legends and myths through their relationship the most important of which is the cycle of stories about King Solomon who built of the Temple of Jerusalem and the spirit of which the Dreamer compares himself with.